(untitled) (Journal of Human Sciences, 2024)
Spatal and lysis of bakeries in the city of sebbausing geographic in formation sgstems.Astady in the geograbhy phy of serries summary, This researchaims to know the patterns of gegraphical. Distribution of bakeries in the city of sebuha .The reality of othe spatial distribution of these bakeries .Therough the use of geogra phical in formation systms (GIS). And an explanation of the current distribution paftern ofbakeries and it is realation ship to some geographical variablas. The research relied on the descriptive and analytical approah in addition to the use of geographic formation systems te chnology. Suchas naalyzing The standad distanca.The average center.The average parameter .The nieghbor hood connention, and The moran coefficient,to determine The mostimportant bakeries and The extent of ,problems facing compliance with planning standards for bakeries for residents of The city of sebha The research shoued that approximately haif. Bakries are concent rafed in the localities of ALManshiya and ALQardah,equiralent to 41.2% of the total number of bakeries in the city of sebha. It was also shown that the geogrephical distribution of bakeries takesa clustered pattern tending toa regular patten according to The nearest neighbor analysis,and the distribution of the phenomenon trends from The north west to The sontheast according to The analysis of The direction of distribution and that the middle center Is located in the centero of The city.(lqaid), and The middle landmark of The phenomenon is located or bakeries, wich reprsent The AL-Alam bakery in The Loca lity of AL-Qarada It also takes The scattered patternwhen andlyzing moran. Thus,we find that through spatial analyzes it indicates The regularity of the distribution of bakeries and that they are clustered in places and not present in places